Alphavirus infection and nociception: differential effects on primary mouse dorsal root ganglia - Katz, Benjamin J. G. (2021)
Alphaviruses such as Chikungunya Virus (CHIKV) and O’Nyong-Nyong Virus (ONNV) present an increasing problem in the world, with an increased vector efficacy allowing infection in previously uninfected areas such as southern Europe and a total infection count of over 5 million in the last 20 years. Most infected patients experience acute pain and a significant proportion go on to develop chronic rheumatoid-like arthritis whose mechanisms remain unclear. One potential target and source of mechanistic insight are the sensory dorsal root ganglia (DRG) that detect peripheral events and propagate nociceptive action potentials for recognition as pain in the CNS. This study aimed to determine if alphaviruses can infect DRGs and if so, which neuronal subpopulations are preferentially infected.